Effect of donor characteristics on T cell‐replete haploidentical stem cell transplantation over the last 10 years at a single institution. (3rd December 2021) - Wu, Yibo; Lai, Xiaoyu; Shi, Jimin; Tan, Yamin; Zhao, Yanmin; Yu, Jian; Liu, Lizhen; Zhang, Wei; Huang, He; Luo, Yi
Summary: One of the most complex issues with haploidentical stem cell transplantation (haplo‐SCT) is donor selection, given that multiple haploidentical donors are often available for a given recipient. To develop evidence‐based guidance for donor selection in the setting of anti‐thymocyte globulin‐based haplo‐SCT, we performed a prospective cohort study of 512 patients with haematological malignancies who had haplo‐SCT to determine which donor variables were most important in favouring transplant outcomes. Increasing donor age was associated with poorer overall survival (OS) [hazard ratio (HR) 1·08, P  = 0·044]. Female donors to male recipients was significantly associated with higher non‐relapse mortality (NRM; HR 2·05, P  = 0·006). Furthermore, increasing donor age had a higher risk of Grades 3–4 acute graft‐ versus ‐host disease (aGVHD; HR 1·17, P  = 0·005), female donors to male recipients was associated with a higher risk of Grades 2–4 aGVHD (HR 1·50, P  = 0·022). Sibling donors had superior OS, disease‐free survival, and NRM than parental donors in patients aged <35 years. However, sibling donors had higher NRM than offspring donors in patients aged ≥35 years. A younger donor, usually a young sibling in younger recipients (aged <35 years) or a young offspring in older patients (aged ≥35 years) and avoiding female donors to male recipients should be preferred when multiple haploidentical donors are available.